2013
DOI: 10.1021/ef301754y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Asphaltene Stability on Fouling at Delayed Coking Process Furnace Conditions

Abstract: In this study, we examine the link between stability of asphaltenes at ambient conditions with fouling at the conditions of a delayed coker furnace, with heat-transfer surfaces above 450 °C. The atmospheric bottom fraction of a crude oil was blended with an aliphatic diluent in different ratios; the S values were measured; and then fouling rates were measured on electrically heated stainless-steel 316 wires in an autoclave reactor. As expected, the less stable the blend, the greater the rate and extent of foul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“…It can be seen that there is considerable These exchangers had 2 tube-passes in the original paper variation in the values so there is a need for more measurements of this thermophysical property. The low value reported by Derakshesh et al (2013) arises from the measurements being made with a heated wire operating at constant heat flux, which promoted vapourisation of the oil in the porous deposit matrix. Equation [4] indicates that this would increase the insulating nature of the deposit significantly.…”
Section: Quantifying the Impact Of Fouling-the Modified Temperature Fmentioning
confidence: 93%
See 1 more Smart Citation
“…It can be seen that there is considerable These exchangers had 2 tube-passes in the original paper variation in the values so there is a need for more measurements of this thermophysical property. The low value reported by Derakshesh et al (2013) arises from the measurements being made with a heated wire operating at constant heat flux, which promoted vapourisation of the oil in the porous deposit matrix. Equation [4] indicates that this would increase the insulating nature of the deposit significantly.…”
Section: Quantifying the Impact Of Fouling-the Modified Temperature Fmentioning
confidence: 93%
“…The deposit thermal conductivity is a material parameter, which is subject to substantial uncertainty. Crude oil deposits vary in composition (oil, metal oxides, carbonaceous material; Derakshesh et al 2013) and λ c is expected to lie in the range 0. (Watkinson and Wilson 1997;Derakshesh et al 2013;Ishiyama et al 2020).…”
Section: Quantifying the Impact Of Fouling-the Modified Temperature Fmentioning
confidence: 99%
“…Under actual conditions in heat transfer equipment, assessing compatibility by fouling is acceptable. Many researchers found that colloidal stability plays a key role in fouling, including Asomaning and Watkinson (2000), Saleh et al (2004), Stark and Asomaning (2003), and Derakhshesh et al (2013). Besides, Srinivasan and Watkinson (2004) stated that fouling is concerned with not only 687 FIGURE 1 Schematic diagram of the fouling loop.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, several studies on crude oil fouling report significant levels of inorganic material, particularly FeS, and these materials will undergo different reaction and ageing pathways to hydrocarbon only materials. For example, Derakshesh et al [17] reported appreciable levels of FeS in deposits under coking conditions and the development of a porous deposit at higher temperatures, which is attributed to subcooled boiling.…”
Section: Distributed Ageing Model (Model Ii)mentioning
confidence: 99%
“…where A is the surface area for heat transfer and W min is the smaller of the two heat capacity flow rates. For a counter current exchanger with W hot = W cold = W min , the effectiveness, , is given by (17) The effectiveness relates the actual heat duty, Q, to the thermodynamically maximum possible duty, Q max , via:…”
Section: Heat Transfer and Foulingmentioning
confidence: 99%